The Factors That Influence Secondary School Students` Academic Motivation in Azerbaijan. - Yusifli, Lala; Alandarova, Sabina; Abbasova, Valida; Beydiyeva, Shirinkhanim (ADA University, 2025)
This qualitative study investigates the factors influencing academic motivation among secondary school students in Azerbaijan, with a particular focus on the roles of psychological, cognitive, social, and environmental variables. While students’ motivation is an extensively studied phenomenon worldwide, there is little literature looking at the specific contextual factors that influence student engagement and motivation in Azerbaijan. To fill this gap, 13 students from three private secondary schools were purposively sampled and participated in semi-structured interviews. The data was transcribed, coded, and thematically analyzed. As part of enhancing the credibility of the findings, memo writing and constant comparison methods were used throughout the analysis. The findings revealed that intrinsic factors—such as personal goals, self-confidence, and self-efficacy—significantly enhanced motivation. Similarly, extrinsic factors, including family support, teacher encouragement, and peer relationships, played a vital role. While technology served as a valuable tool for independent learning, it also emerged as a source of distraction. The study highlights the dual impact of digital integration and underscores the cultural and contextual specificities of academic motivation in Azerbaijan. By addressing a gap in the literature, this research provides actionable insights and a handbook as a final product for educators and policymakers to create more supportive, student-centered, and technologically balanced learning environments that foster sustainable academic motivation.
Keywords: Motivation in education -- Azerbaijan.; High school students -- Psychology.; Academic achievement -- Psychological aspects.; Educational psychology.; Technology in education -- Psychological aspects.; Family support -- Educational aspects.